2012
DOI: 10.1007/s00590-012-1085-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of care pathways for hip fractures: a systematic overview of secondary studies

Abstract: The aim of this paper was to perform a systematic overview of secondary literature studies on care pathways (CPs) for hip fracture (HF). The online databases MEDLINE-PubMed, Ovid-EMBASE, CINAHL-EBSCO-host, and The Cochrane Library were searched. A total of six papers, corresponding to six secondary studies, were included but only four secondary studies were HF-specific and thus assessed. Secondary studies were evaluated for patients' clinical outcomes. There were wide differences among the studies that assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…This routine includes steps such as giving patients with a suspected hip fracture fluids and pain relief in the ambulance and transiting the patient rapidly from the ambulance to the orthopaedic ward directly after radiography. Fast-track care for hip fracture patients can minimise complications, increase priorities and decrease length of stay (LOS) (Hommel et al, 2008;Larsson and Holgers, 2011;Leigheb et al, 2013). Surgery within 24 hours following fracture reduces hospital stay and may also reduce complications and mortality (Al-Ani et al, 2008;Simunovic et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This routine includes steps such as giving patients with a suspected hip fracture fluids and pain relief in the ambulance and transiting the patient rapidly from the ambulance to the orthopaedic ward directly after radiography. Fast-track care for hip fracture patients can minimise complications, increase priorities and decrease length of stay (LOS) (Hommel et al, 2008;Larsson and Holgers, 2011;Leigheb et al, 2013). Surgery within 24 hours following fracture reduces hospital stay and may also reduce complications and mortality (Al-Ani et al, 2008;Simunovic et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Leighbeg et al 67 found no clear evidence of reduced mortality from their systematic overview of four secondary studies investigating the effect of care pathways and/or multidisciplinary team care approaches for people following hip fracture. However, diversity of study settings and difficulty with classification of studies in relation to the status of their interventions (care pathways or not care pathways) may have influenced the findings.…”
Section: Resultsmentioning
confidence: 95%
“…Multisiciplinary team32 care was defined as care provided by two or more different care practitioners working together as/or supported by a multidisciplinary team. Selected publications focused on orthogeriatric inpatient care,32 65 fracture liaison services (FLS)25 66 and care pathways for people following hip fracture 67…”
Section: Resultsmentioning
confidence: 99%
“…Our protocol emphasizes early mobilization with unrestricted weight bearing. Early mobilization in elderly hip fracture patients has been shown to improve mortality, morbidity and accelerate functional recovery [8, 9, 22, 23]. Limiting weight bearing status after surgery complicates the recovery period by prolonging dependency on walking aids and the need for the patient to remain in an extended care facility [47].…”
Section: Discussionmentioning
confidence: 99%